Pengaruh Citra Merek Dan Kestrategisan Lokasi Terhadap Minat Beli Keanggotaan Pada Rancamaya Golf And Country Club - Maryana, Hesti; Fadillah, Adil (Jurnal Ilmiah Pariwisata Kesatuan, 2022)
Very high business competition at this time occurs between companies encouraging companies to be able to compete with each other in activities for the development of the target market. In a service company, a marketing strategy is very necessary, because it includes the entire plan in its business unit to make changes from potential buyers to buyers who can feel the benefits of their products. In service products, especially in the provision of sports facilities, which are usually the determining factors for consumers in making their choices are the brand image and strategy of their business location. The purpose of this study is to determine (1) the influence of brand image on the buying interest of membership at Rancamaya Golf and Country Club, (2) the effect of the strategicity of location on membership buying interest in Rancamaya Golf and Country Club, (3) the influence of brand image and location strategy on membership buying interest in Rancamaya Golf and Country Club. The author conducted research at Rancamaya Golf and Country Club, which is located on Jalan Rancamaya Utama, Ciawi – Bogor. The method used in this study is a survey and verifiable method. Respondents numbered 94 using the Slovin Technique taken from members at Rancamaya Golf and Country Club. The research data was processed using SPSS Version 25. Based on the results of the study, it is known that (1) Brand image has a positive and significant effect on the interest in buying membership at Rancamaya Golf and Country Club, which means that the test results support the H1 research hypothesis, so that the H1 hypothesis is accepted (2) the strategicity of the location has a positive and significant effect on the interest in buying membership at Rancamaya Golf and Country Club, which means that the test results support the H1 research hypothesis, so that the H1 hypothesis is accepted. (3) The results of the F-test study showed that the F-value or prob value (0.000) < alpha 5% was rejected, so it was rejected by H0, it means that the Brand Image (X1) and The Strategicity of The Location (X2) affected the Buying Interest (Y). Thus, the test results support the H1researchhypothesis:β1,β2≠0(thereisarelationshipbetweenXandY),it meansthattheBrandImageand The Strategicity of The Locationvariables haveasimultaneousinfluenceonBuyingInterest. Keywords: Brand Image, Location Strategy, Buying Interest